An investigation of metastatic colorectal cancer - Asiri, Abutaleb (2018)
Colorectal cancer (CRC) is the third most common cancer worldwide and the fourth most common cause of death. This complex disease process starts in the colon or rectum, as a non-cancerous polyp which can become malignant over time. In the later stages of CRC, tumour cells become detached from the primary tumour, migrate and enter the blood or lymphatic vessels and ultimately form a secondary tumour at another site (distant metastasis). CRC metastasis may also arise from residual tumour cells that persist after treatment.